2006
DOI: 10.1073/pnas.0602318103
|View full text |Cite
|
Sign up to set email alerts
|

Hotspots for copy number variation in chimpanzees and humans

Abstract: Copy number variation is surprisingly common among humans and can be involved in phenotypic diversity and variable susceptibility to complex diseases, but little is known of the extent of copy number variation in nonhuman primates. We have used two array-based comparative genomic hybridization platforms to identify a total of 355 copy number variants (CNVs) in the genomes of 20 wild-born chimpanzees (Pan troglodytes) and have compared the identified chimpanzee CNVs to known human CNVs from previous studies. Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
200
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 210 publications
(214 citation statements)
references
References 55 publications
14
200
0
Order By: Relevance
“…Combining all zebrafish CNVs discovered, a nonredundant dataset comprising 192,460,331 bp of sequence, representing 14.6% of the zebrafish reference genome, was obtained. This dataset represents more than four times the percentage of reference genome sequence covered by similarly common CNVs in humans (4) and other vertebrates (5,8,9). Reporting the percentage of the genome affected by CNVs should compensate for differences in genome sizes and array resolutions from different CNV studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Combining all zebrafish CNVs discovered, a nonredundant dataset comprising 192,460,331 bp of sequence, representing 14.6% of the zebrafish reference genome, was obtained. This dataset represents more than four times the percentage of reference genome sequence covered by similarly common CNVs in humans (4) and other vertebrates (5,8,9). Reporting the percentage of the genome affected by CNVs should compensate for differences in genome sizes and array resolutions from different CNV studies.…”
Section: Resultsmentioning
confidence: 99%
“…Structural genomic variants, including both balanced (e.g., most inversions, insertions, and translocations) and unbalanced rearrangements (i.e., copy number variants; CNVs), are widespread among vertebrates, with CNVs representing the largest known component (4)(5)(6)(7)(8)(9)(10)(11). In addition, CNVs have also been associated with human disease phenotypes including neurological disorders (12), early onset obesity (13), and some forms of cancer (14).…”
mentioning
confidence: 99%
“…For example, it has been reported in a study that segmental duplication events are found to be affecting the genome variability greater than single base-pair change in chimpanzee and human genomes. [71][72][73] CNV distribution among various populations should pave the way to understand evolution and mechanism of development of newer CNV. Finally, it is very important to take in account all structural variations to fully understand the mechanism underlying the phenotype, disease development and human diversity.…”
Section: Future Perspectivementioning
confidence: 99%
“…Indeed, copy-number variants (CNVs; sometimes also called 'copy-number polymorphisms' or CNPs) have been shown to be widespread in a variety of organisms, including humans (Sebat et al 2004;Conrad et al 2006;McCarroll et al 2006;Redon et al 2006), mice (Graubert et al 2007;She et al 2008), chimpanzees (Perry et al 2006, rhesus macaques (Lee et al 2008), cows (Liu et al 2010), dogs (Chen et al 2009;Nicholas et al 2009), chickens (Griffin et al 2008), maize (Springer et al 2009), Arabidopsis thaliana (Ossowski et al 2008), fruitflies (Dopman & Hartl 2007;Emerson et al 2008), Caenorhabditis elegans (Maydan et al 2010) and Saccharomyces cerevisiae (Carreto et al 2008). Though it is often harder to experimentally identify and genotype CNVs relative to SNPs and indels, many are big enough to encompass whole genes and are therefore more likely to affect organismal fitness.…”
Section: Introductionmentioning
confidence: 99%